Static Analysis and Experimental Validation of Containerized Fire Pump Stations - Firmansah; Adyana; T. Ardiansyah (Jurnal Locus Penelitian dan Pengabdian, 2026)
Containerized fire pump stations repurpose ISO 40ft High Cube containers but require large openings for ventilation and access, altering structural stiffness. his study evaluates a modified container under three load cases: LC2 (dynamic lifting, 1.2g), LC3 (static operation), and LC4 (2-tier stacking, 1.8g). A mesh convergence study established a reference mesh with maximum element size h = 20 mm. Validation was performed by comparing incremental deflections at six measurement points (T1–T6) between FEA and a workshop static test under LC3, using Mean Absolute Percentage Error (MAPE) as the accuracy metric. The validated model achieved a global MAPE (T1–T4) of 10.01%, indicating adequate agreement in global stiffness. For the reference mesh, key results are: LC3 – ovm,max = 161.56 MPa, omax = 2.69 mm, SFdesign,min = 1.55; LC2 – ovm,max = 236.71 MPa, omax = 3.40 mm, SFdesign,min = 1.14; LC4 – ovm,max = 296.21 MPa, omax = 2.86 mm, SFdesign,min = 1.16. Stress hotspots are localized around openings, showing indications of spot stress/singularity; therefore, structural interpretation focuses on global response and nominal stresses in primary load-carrying members. The integration of NFPA 20 ventilation and access requirements with ISO 1496-1-based structural assessment is feasible using a validated FEA model. The modified container meets yield and deflection limits, providing defensible operational limits for lifting and 2-tier stacking under controlled dynamic factors.